2014
DOI: 10.1590/s0103-90162014000200010
|View full text |Cite
|
Sign up to set email alerts
|

Ozonated water and chlorine effects on the antioxidant properties of organic and conventional broccoli during postharvest

Abstract: There is growing interest in studies on sanitizers other than chlorine that can maintain the quality of organic products without affecting their phytochemical content. The effects of using chlorinated and ozonized water treatments, as sanitizing procedures, on the post-harvest quality of organic and conventional broccoli (Brassica oleracea L.) cv. Italica was evaluated. The biochemical parameters (chlorophyll, polyphenols, fl avonoids, vitamin C and antioxidant capacity) of the broccoli samples were analyzed a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 21 publications
1
8
0
1
Order By: Relevance
“…Palmer, with or without sanitization during the storage in cold chamber or simulated marketing. Other studies have confirmed the efficiency of using ozone for sanitation (Karaca and Velioglu, 2007), as reported for broccoli (Lima et al, 2014) and papaya (Yeoh et al, 2014).…”
Section: Microbiological Analysessupporting
confidence: 55%
See 2 more Smart Citations
“…Palmer, with or without sanitization during the storage in cold chamber or simulated marketing. Other studies have confirmed the efficiency of using ozone for sanitation (Karaca and Velioglu, 2007), as reported for broccoli (Lima et al, 2014) and papaya (Yeoh et al, 2014).…”
Section: Microbiological Analysessupporting
confidence: 55%
“…To sanitize vegetable foods, some products including chlorine gas, sodium or calcium hypochlorite and organic chlorine should be avoided because they form carcinogenic chlorinated compounds such as trihalomethanes that cause serious problems to human health and the environment (Yeoh et al, 2014). In this context, ozonated water has emerged as a safe form of sanitization in various plant products such as broccoli (Lima et al, 2014), honey pineapple, banana, and guava (Alothman et al, 2010), papaya (Yeoh et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many fresh-to-eat food products showed an antioxidant increase after ozone treatment in a modified atmosphere [36,37], whereas in terms of ozonized water, the answer seems to be also linked to the species used. Some experiments [34] reported that treating broccoli with ozonized water did not alter phenols and antioxidants content. In this experiment, instead, the water treatment increased the amount of antioxidants in the whole plant and the commercial product.…”
Section: Production and Quality Aspects Of Rttmentioning
confidence: 99%
“…However, O 3 is often employed directly on the product in gaseous form, with modified atmosphere [31], or as a disinfection treatment in fresh-to-eat products [32,33]. Limited are the studies that evaluate the use of ozone in the water where the product is dipped [34,35] and, to our knowledge, there is no information about plant growing inside ozonized water. Some recent studies used ozone for nutrient solution sanitization in hydroponics [14], but no reference is made to the product quality.…”
Section: Production and Quality Aspects Of Rttmentioning
confidence: 99%